Measurement of the production cross-section of ψ(2S) →J/ψ (→ μ+μ¯)π+ π¯ in pp collisions at √s = 7 TeV at ATLAS - Alconada Verzini, María Josefina (2014)
The prompt and non-prompt production cross-sections for ψ(2S) mesons are measured using 2.1 fb−1 of pp collision data at a centre-of-mass energy of 7TeV recorded by the ATLAS experiment at the LHC. The measurement exploits the ψ(2S) → J/ψ (→ μ+μ¯)π+ π¯ decay mode, and probes ψ(2S) mesons with transverse momenta in the range 10 ≤ pT < 100 GeV and rapidity |y| < 2.0. The results are compared to other measurements of ψ(2S) production at the LHC and to various theoretical models for prompt and non-prompt quarkonium production.